Asuhan Keperawatan pada Tn. H dengan Gangguan Sistem Kardiovaskular: Congestive Heart Failure (CHF) di Ruang Dahlia RSUD dr. Soeselo Kabupaten Tegal - M Ragil Bahtiar Rizqi; Tati Karyawati; Muhammad Silahudin (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Heart failure or congestive heart failure (CHF) is a condition where the heart is unable to pump blood optimally to meet the body's metabolic needs, resulting in symptoms such as shortness of breath, excessive fatigue, and edema (Majid, 2017). According to WHO data in 2023, CHF is one of the main causes of death with a total of 17.5 million deaths from a total of 58 million cases recorded worldwide. This paper aims to describe and provide an overview of nursing care for patient Mr. H who experiences cardiovascular system disorders in the form of CHF in the Dahlia room of Dr. Soeselo Regional Hospital, Tegal Regency in accordance with nursing practice standards. The method used is a descriptive method through a case study with data collection techniques using interviews and observations. From the results of the case review, the main complaint experienced by the patient was shortness of breath which was quite disruptive to daily activities. Based on this condition, four main nursing diagnoses were found, namely ineffective airway clearance, hypervolemia, activity intolerance, and knowledge deficits related to the disease and self-care. The interventions provided are based on theoretical references in the Indonesian Nursing Diagnosis Standards (IDHS) and the Indonesian Nursing Outcome Standards (SLHS), and are tailored to the patient's actual condition. The implemented action plan is expected to help reduce symptoms, improve the patient's ability to function, and provide a better understanding of CHF so that the patient can actively participate in the care process.